Analisis Kandungan Asam Askorbat Dalam Buah Salak (Salacca Zalacca) Dengan Iodometri: Analisis Kandungan Asam Askorbat Dalam Buah Salak (Salacca Zalacca) Dengan Iodometri - Diningsih, Ayus - (Jurnal Kesehatan Ilmiah Aufa Royhan, 2019)
Analysis of ascorbic acid content in Padangsidimpuan zalacca fruit (Salacca Zalacca) with iodometry was carried out. The purpose of this research was to determine ascorbic acid levels contained in zalacca fruit. This research method was laboratory experimental. The analysis process was carried out using the iodometric titration method on Padangsidimpuan zalacca (Salacca Zalacca) samples with variations in storage time. The results of the research stated that the content of vitamin C in Padangsidimpuan zalacca fruit (Salacca Zalacca) decreased from the first day (2.158mg / 100 gram sample), the second day (1,825 mg / 100 gram sample), the third day (1,740 mg / 100 gram sample) , the fourth day (1,686 mg / 100 gram sample), the fifth day (1,520 mg / 100 gram sample), the sixth day (1,372 mg / 100 gram sample), the seventh day (1,020 mg / 100 gram sample) and the day of the traffic (0,897 mg / 100 gram sample). Decreased vitamin C content in Padangsidimpuan zalacca fruit (Salacca Zalacca) due to vitamin C is easily oxidized or degraded, either by temperature, light or ambient air so that vitamin C levels are reduced.